Calibration method for the rotating axis in panoramic 3D shape measurement based on a turntable. (11th December 2020) - Cai, Xiaoqi; Zhong, Kejun; Fu, Yanjun; Chen, Jianbin; Liu, Yanzhao; Huang, Chunzhi
Abstract: In panoramic three-dimensional (3D) shape measurement based on a turntable, the point cloud registration accuracy is greatly affected by the calibration of the rotating axis. To improve the calibration accuracy of the rotating axis, a calibration method based on an auxiliary camera is proposed. The calibration procedure uses a checkerboard and an auxiliary camera. Firstly, the checkerboard is rotated on the turntable to determine the rotation axis, and is used to calibrate the relative orientation of the auxiliary camera and the measurement camera, so that the two cameras have the same world coordinate system. Then, the origin point of the coordinate of the rotation axis is obtained by the auxiliary camera, and the Z -axis direction is taken as the direction of the rotation axis. Finally, the 3D shape of the multi-view is measured by the fringe projection system, and the rotation registration is completed according to the rotation axis vector. The proposed method does not need to reconstruct the 3D coordinates of multiple points when the rotating axis is calibrated. The experimental results show that the proposed method effectively improves the calibration accuracy of the rotation axis vector, and reduces the complexity of the calibration process.